Traduire, c'est à dire... Phénoménologies d'un concept pluriel - Ladmiral, Jean-René (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1995)
AbstractThe author proposes a three-dimensional analysis, which he refers to as "trois phénoménologies distinctes", to discuss the thorny issue of defining translation. First, within the framework of a linguistic or semantic phenomenology, he looks at the different uses of the term "translation". Second, he uses a psychological phenomenology to examine the psycho-linguistic functions. Finally, he resorts to a philosophical phenomenology to study the parameters and the limits when it comes to conceptualizing translation.